Macrocyclic Arenes‐Based Conjugated Macrocycle Polymers for Highly Selective CO2 Capture and Iodine Adsorption - Dai, Dihua; Yang, Jie; Zou, Yong‐Cun; Wu, Jia‐Rui; Tan, Li‐Li; Wang, Yan; Li, Bao; Lu, Tong; Wang, Bo; Yang, Ying‐Wei (Angewandte Chemie International Edition, 2021)
Incorporating synthetic macrocycles with unique structures and distinct conformations into conjugated macrocycle polymers (CMPs) can endow the resulting materials with great potentials in gas uptake and pollutant adsorption. Here, four CMPs (CMP‐n, n=1–4) capable of reversibly capturing iodine and efficiently separating carbon dioxide are constructed from per‐triflate functionalized leaning tower[6]arene (LT6‐OTf) and [2]biphenyl‐extended pillar[6]arene (BpP6‐OTf) via Pd‐catalyzed Sonogashira–Hagihara cross‐coupling reaction. Intriguingly, owing to the appropriate cavity size of LT6‐OTf and the numerous aromatic rings in the framework, the newly designed CMP‐4 possesses an outstanding I2 affinity with a large uptake capacity of 208 wt % in vapor and a great removal efficiency of 94 % in aqueous solutions. To our surprise, with no capacity to accommodate nitrogen, CMP‐2 constructed from BpP6‐OTf is able to specifically capture carbon dioxide at ambient conditions. Four catcher‐type conjugated macrocycle polymers (CMP‐n, n=1–4) have been designed and synthesized successfully, exhibiting interesting application in CO2 and I2 uptake. The CMP‐2 is able to capture CO2 with excellent selectivity and the CMP‐4 is capable of adsorbing iodine with outstanding capacity.